Strengthening Students' Religious Character: Case Study in Public Islamic Elementary School - Sulistyani Sulistyani; Atim Rinawati; Benny Kurniawan; Ali Mahfudz; Siti Fatimah (Yayasan Arfah Bin Haji Muhammad Saleh, 2026)
This research aims to analyze the formation of religious character in students at MIN 3 Banjarnegara. This study employs a qualitative approach with a case study type. Data collection techniques include observation, interviews, and documentation. Data analysis utilizes the Miles & Huberman & Saldana model, consisting of three stages: data condensation, data display, and data verification. The research findings indicate that: 1) Student development in strengthening religious character is carried out through curricular and extracurricular activities; 2) Providing special activity services; 3) Self-development initiatives; 4) Implementing habituation activities and fostering a school culture. Supporting factors for the program include: Support from all stakeholders (parents, community), a positive and religious environment that greatly aids in instilling religious values, and a curriculum integrated with religious values. Meanwhile, inhibiting factors in student character formation are: The rapid development of technology, which influences student character education, and a less supportive social environment/peer group.